How are bodies special? Effects of body features on spatial reasoning. Issue 6 (June 2016) - Yu, Alfred B.; Zacks, Jeffrey M.
Embodied views of cognition argue that cognitive processes are influenced by bodily experience. This implies that when people make spatial judgments about human bodies, they bring to bear embodied knowledge that affects spatial reasoning performance. Here, we examined the specific contribution to spatial reasoning of visual features associated with the human body. We used two different tasks to elicit distinct visuospatial transformations: object-based transformations, as elicited in typical mental rotation tasks, and perspective transformations, used in tasks in which people deliberately adopt the egocentric perspective of another person. Body features facilitated performance in both tasks. This result suggests that observers are particularly sensitive to the presence of a human head and body, and that these features allow observers to quickly recognize and encode the spatial configuration of a figure. Contrary to prior reports, this facilitation was not related to the transformation component of task performance. These results suggest that body features facilitate task components other than spatial transformation, including the encoding of stimulus orientation.